2015
DOI: 10.1007/s11325-015-1153-7
|View full text |Cite
|
Sign up to set email alerts
|

Severe obstructive sleep apnea increases left atrial volume independently of left ventricular diastolic impairment

Abstract: Severe OSA itself might directly increase LAVI, independently of LV diastolic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Left atrial (LA) dilation is associated with various cardiac disorders, such as valvular heart diseases [1, 2], left ventricular (LV) systolic [3] or diastolic dysfunction [4], obstructive sleep apnea [5, 6], and atrial fibrillation [79]. LA enlargement is a risk marker for the future development of atrial fibrillation [8, 10], and is associated with heart failure hospitalizations, stroke [11, 12], and death [1315].…”
Section: Introductionmentioning
confidence: 99%
“…Left atrial (LA) dilation is associated with various cardiac disorders, such as valvular heart diseases [1, 2], left ventricular (LV) systolic [3] or diastolic dysfunction [4], obstructive sleep apnea [5, 6], and atrial fibrillation [79]. LA enlargement is a risk marker for the future development of atrial fibrillation [8, 10], and is associated with heart failure hospitalizations, stroke [11, 12], and death [1315].…”
Section: Introductionmentioning
confidence: 99%
“…An increased AHI was associated with decreased mitral E wave [9] and increased mitral A wave velocities [9, 17] (Table 4). Although Varghese et al did not find a significant difference regarding mitral E/A ratio in patients with severe OSA (1.1 ± 0.2) versus controls (1.2 ± 0.2; p =0.09) [10], several other studies reported that mitral E/A ratio decreases with OSA severity [9, 13, 17]. Surprisingly, Altekin et al found significantly lower E/A ratio only in patients with mild OSA ( p =0.0009) but not in subjects with moderate or severe OSA [11].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that OSAHS treatment might reduce the risk of cardiovascular complications. CPAP treatment has been proven to reduce blood pressure 5,20 and correct left ventricular hypertrophy and systolic and diastolic dysfunctions caused by OSAHS 21,22 . There were limited data on the effects of oral appliance treatment on cardiac function.…”
mentioning
confidence: 99%